2005
DOI: 10.1111/j.1471-0528.2005.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent urinary incontinence and delivery mode history: a six‐year longitudinal study

Abstract: Objective To investigate the prevalence of persistent and long term postpartum urinary incontinence and associations with mode of first and subsequent delivery.Design Longitudinal study.Setting Maternity units in Aberdeen (Scotland), Birmingham (England) and Dunedin (New Zealand).Population Women (4214) who returned postal questionnaires three months and six years after the index birth.Methods Symptom data were obtained from both questionnaires and obstetric data from case-notes for the index birth and the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 33 publications
9
117
3
5
Order By: Relevance
“…21 Multiple logistic regression of persistent UI showed that compared to single vaginal delivery, women who had multiple deliveries had higher incidence of UI. 22 Odds ratio is higher for increase in number of deliveries. Odds of UI was 1.36 (95% CI-1.06-1.74; P value-0.015) in women who had 2 deliveries, in those with 3 deliveries had OR of 1.85 (95% CI-1.42 -2.42; P value < 0.001), whereas in those with four or more deliveries had OR of 2.16 (95% CI-1.57-2.97; P value < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…21 Multiple logistic regression of persistent UI showed that compared to single vaginal delivery, women who had multiple deliveries had higher incidence of UI. 22 Odds ratio is higher for increase in number of deliveries. Odds of UI was 1.36 (95% CI-1.06-1.74; P value-0.015) in women who had 2 deliveries, in those with 3 deliveries had OR of 1.85 (95% CI-1.42 -2.42; P value < 0.001), whereas in those with four or more deliveries had OR of 2.16 (95% CI-1.57-2.97; P value < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A study in 4200 women conducted six years after delivery showed that those that had only vaginal delivery and those that had delivered both vaginally and by cesarean section had an approximately equal prevalence of urinary leakage (26% and 28%, respectively). However, the prevalence among those having delivered only by cesarean section was 14% 35 . A large retrospective population-based observational study 12 in a population of 15,300 women found the prevalence of urinary leakage of 10% in the nulliparous group and 16% in the cesarean section group, while in the group that had only vaginal deliveries the rate was 24%.…”
Section: Impact Of Pregnancy and Delivery On Urinary Incontinencementioning
confidence: 99%
“…Th is research implies that cesarean delivery might not protect against urinary incontinence 12 . It appears that a woman must have all children delivered by cesarean section in order to achieve protection against long-term incontinence 35 . Urinary incontinence in pregnancy increases the risk of later urinary incontinence, both postpartum and later in life 17,38 , but nevertheless it is not a predictor of benefi t from giving birth by cesarean section to protect against urine leakage 17,39 .…”
Section: Impact Of Pregnancy and Delivery On Urinary Incontinencementioning
confidence: 99%
“…17 There may also be an increased risk of urinary incontinence, although this may be more closely associated with a longer second stage of labour; 18,19 however, women who have a caesarean section have a lower risk of symptoms. 20,21 Other bowel problems such as haemorrhoids 19,22,23 and constipation 24 are more common after IVD, as are perineal pain and dyspareunia. 24,25 Caesarean section has many adverse sequelae, but, with the exception of faecal incontinence, most of these symptoms are less likely to occur in association with this delivery mode.…”
Section: Scientific Backgroundmentioning
confidence: 99%